Analysis of perception and emotional condition from distance learning among undergraduate student during Covid-19 pandemic - Liza, Rini Gusya; Fasrini, Ulya Uti; Wati, Westi Permata (International Journal of Research in Counseling and Education, 2021)
Education minister changes learning methodby distance learning to prevent the spread of Covid-19. This change has an impact on the mentality of students. This research aims to analysis perception and emotional mental health of undergraduate students at the Faculty of Medicine, Universitas Andalas during the Covid-19 pandemic. This research is cross-sectional study and obtained 344 respondents using simple random sampling from May to December 2020. The distance learning evaluation use questionnaire in google form and the results are quantitative data; the emotional mental health condition use SRQ-20 and Microsoft Excel. This result show that all respondents experienced mental emotional disorders. The most frequently is cognitive symptoms, but some students still enjoy because closed to their family and cost saving although they have some obstacles observed, both in terms of devices, signal, and lack of interaction. All of students have mental health disorder but distance learning has been running well.